The Effect of Auditor's Intention to Use CAATs on Self-Efficacy as a Moderating Variables in UTAUT 3 (E-Jurnal Akuntansi, 2026)
The progress of audit technology has encouraged the increased use of CAATs as a means of strengthening audit performance and quality. This paper aims to analyze the elements affecting auditors’ motivation to utilize CAATs through the UTAUT 3 model, moderated by self-efficacy. Data was gathered using questionnaires given to auditors who work at public accounting firms in Semarang City, involving a total sample of 223 respondents. The data was analyzed using the Partial Least Square-Structural Equation Modeling method, also known as PLS-SEM. All UTAUT 3 framework factors are confirmed to influence auditors' intention to adopt CAATs, with social influence and performance expectancy appared as the leading factors. Self-efficacy strengthens the relationships between several variables and intention. The evidence reinforces the significance of behavioral and psychological factors in supporting the adoption of audit technology.
Keywords: Intention to Use; CAATs; UTAUT3; Self-Efficacy